Neurophysiological Synchrony Between Children With Severe Physical Disabilities and Their Parents During Music Therapy - Samadani, Ali; Kim, Song; Moon, Jae; Kang, Kyurim; Chau, Tom (Frontiers in Neuroscience, 2021)
Although physiological synchronization is known to be highly associated with the level of empathy in emotionally meaningful relationships, little is known about the physiological attunement between children with severe disabilities and their caregivers. We investigated the degree of child-parent neurophysiological synchronization in 10 child-parent dyads, where the child was non-verbal with severe motor disabilities. Synchrony was quantified via measurements of spectral coherence and Granger causality between child and parent electroencephalographic (EEG) activities during 10 music therapy sessions. Significant child-parent interbrain synchronization at different frequency bands and brain regions were detected using cluster-based permutation tests. Brain region, frequency band and the direction of interbrain coupling were found to have significant effects on the resulting dyadic coherence and Granger influences. A significant dyadic coherence was observed between children’s right frontal and parent’s left frontal regions at $β$ and lower $γ$ bands in empathy-related brain regions. Furthermore, significant Granger influences were detected in both directions (from child to parent and vice versa) at $β$ and lower $γ$ bands. In all dyads, significant increases in session-specific coherence and Granger influences were observed at $β$ and lower $γ$ bands toward the end of the session. The observed child-parent interbrain couplings suggest a music therapy-mediated, shared empathic experience between nonverbal children and their parents.